Perubahan Perilaku Konsumen Dari Generasi Milenial Akibat Menggunakan Aplikasi Go-Food - Amalia Rosyadi Putri (Dakwatuna: Jurnal Dakwah dan Komunikasi Islam, 2019)
Industrialization, individualism, information, and investment support technological advancements that have triggered increasingly intense economic globalization. The benefits of the internet have brought many people connected to the internet and consumers are starting to make online purchases through the internet. Based on the results of a survey conducted by APJII 2016 it can be seen that the largest internet users in Indonesia are in the age range of 25-29 years and 35-39 years, which in that range is a range that is classified as young people or can be said to enter the "milineal generation" or " generation Y ". This smart generation is technologically they grew up in the information age and tend to use media as a daily basis. This is believed to be the largest group of people who use the internet as a shopping channel. Including, making transactions through the Go-Food application to order food and drinks. There is a change in consumer behavior in millennial generation. Before Go-Food, they still traded food conventionally, turning into online transactions, in their habits. Key words: Consumer Behavior, Go-Food Applications, Technology, Millennials